Achieving educational innovation for sustainable development between developing and developed countries - Quirós-Alpera, Susana; Roets, Aloysius OSB; Robina Ramírez, Rafael (GRAÓ, 2025)
Humanity’s escalating ecological crisis reflects a culturally ingrained lack of respect, care and connection with the natural world. Industrialised societies have increasingly estranged human communities from nature, viewing environments as storehouses of resources for exploitation or as threats to be conquered. Attaining sustainable development globally obliges widespread educational shifts in how societies perceive relationships and responsibilities toward the natural world. As the sustainability crisis mounts globally, transitioning to environmentally regenerative and socially just development models depend on educational transformations across all nations regarding human-nature mentalities. Significant divergence exists between Western industrialised and Global South countries in orientations shaping ecological perspectives. Analysing contrasts provides mutual learning opportunities to progress global sustainability. While risks of generalization exist, the above synthesis highlights how divergent socioeconomics, cultural traditions, economic infrastructures and colonial legacies shape sustainability perspectives and duties asymmetrically across national contexts. Education is increasingly seen as crucial for equipping new generations to solve complex sustainability challenges like climate change, environmental degradation, and social inequality. Innovating sustainable education systems requires substantial change at multiple scales with no one-size-fits-all model across varying contexts (Sterling et al., 2022). Effectively teaching sustainability across global contexts obliges adapting educational approaches to account for divergent national attributes impacting environmental perspectives and appropriate school sustainability curriculum design and teaching practices. While developed countries possess abundant resources for pioneering sustainability education (ESD) technologies, developing communities with fewer means often most urgently require solutions to climate threats intensifying poverty. Achieving internationally collaborative ESD innovation hinges on equitable two-way technology transfer and contextualization. Funding shortfalls, electricity instability and limited digital access in marginalised regions constrain cutting-edge EdTech integration (Tembe, 2022). However, contextual frugality also gives rise to resilient design innovations like decentralized community knowledge hubs run on solar that wealthier institutions could emulate (Cobbinah y Darkwah, 2021). Hence developing countries should be viewed as partners holding sustainability wisdoms, not just beneficiaries. Meanwhile educational models utilising developing cultures could guide urban schools struggling with student eco-anxiety (Mogusu et al., 2019; Higde, 2022). So instead of imposing non- situated ideas, innovations should build inter-cultural sustainability mindsets by exchanging regionally-attuned pedagogies internationally through global forums in developing cultures (Sterling et al., 2022). Furthermore, virtual exchange programs between demographics like rural farmers and urban students foster mutual learning (Falk et al., 2021). Developing communities share traditional ecological knowledge about seed saving, collective land stewardship and resilience practices to enrich redesigned ESD curricula, grounded in diverse lived wisdom worldwide (Brondizio et al., 2021). Blending developed and developing countries educational teaching in sustainability strengths thereby promises a proliferation of globally-responsive sustainability education capabilities across contexts. Equitable international collaboration around educational innovation for sustainable development requires humility. While resourced institutions can offer platforms for scalable technology exchange, grass-roots community voices should lead in guiding relevant solutions. The objectives of the paper are twofold: 1. Analysing specialised literature on the topic of educational innovation for sustainable development between developed and developing countries. 2. Extracting hypotheses out of the literature review to build a model on the topic.
Es un capítulo del libro: Gavilán, D., Baena, S., Quirós, S., Álvarez, J.F. Educación transformadora: innovación y didáctica para la sostenibilidad. GRAO.
Keywords: educational innovation; developing and developed countries